The Impact of Public Figures, Words, and Ads on Esse Cigarette's International Marketing Strategy - Lambok Manurung (Sinergi International Journal of Economics, 2024)
This study investigates the influence of public figures and word choice in marketing strategies on consumer behavior, particularly in the tobacco industry in Indonesia. Focusing on the Esse cigarette brand by KT&G, the research explores how celebrities and commercial advertising influence consumer perceptions and purchasing decisions. The study addresses the research problem of understanding the combined impact of public figures and language in marketing on consumer behavior, specifically in the context of kretek cigarettes. Using a qualitative approach and an exploratory, descriptive method, data were collected through in-depth interviews with 50 active smokers and ten retail outlets in Jakarta, Surabaya, Medan, and Makassar. Thematic analysis was applied to interpret consumer experiences and perceptions. The results reveal that using personal language in copywriting, emotional taglines, and celebrities as brand ambassadors significantly increases consumer interest and purchasing decisions. Television and social media ads were identified as the most influential media, with a 25% increase in sales following celebrity endorsements. The study concludes that marketing strategies utilizing emotional appeals and public figures effectively enhance consumer engagement and drive sales, particularly in Indonesia’s competitive cigarette market.